Estimating the Role of Climate Change on International Tourism Flows: Evidence Form Regional Panel - Cizrelioğulları, Mehmet Necati (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
This study examines the role of climate changes on international tourist flows using regional panel. Initial examination has been done using regional and income group classifications while in the second stage small islands have been considered as sun beach destinations. Results prove our research question that climate changes exert significant effects on international tourist flows. These effects are positive in small islands while they are mixed of sings in the cases of regional and income groups classifications. In some developed regions such as Central Europe and the Baltics, a significant interaction between climate changes and tourist flows could not be obtained. Major results of this study contains important policy implications as discussed during this research.

ÖZ: Bu çalışma da, bölgesel panel kullanılarak iklim değişikliğinin uluslararası turizm akımları üzerindeki rolü incelenmiştir. İlk aşamada, bölgesel ve gelir grubu sınıflandırmaları kullanılarak yapılırken, ikinci aşamada ise küçük adalar (Malta, Kuzey ve Güney Kıbrıs) güneş ve sahil yerleri olarak kabul edilmiştir. Elde ettiğimiz sonuçlar neticesinde, iklim değişikliğinin uluslararası turist akışları üzerinde önemli etkiler yarattığı görülmektedir. Bu etkiler, küçük adalarda olumlu bir şekildeyken, bölgesel ve gelir grupları sınıflandırmalarında karışık olduğundan kesin birşey söylemek zordur. Orta Avrupa ve Baltıklar gibi bazı gelişmiş bölgelerde, iklim değişikliği ile turist akışları arasında önemli bir etkileşim elde edilememiştir. Bu çalışmanın ana sonuçları, bu araştırma sırasında tartışıldığı gibi önemli politika sonuçları içermektedir.
Doctor of Philosophy in Tourism Management. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Tourism, 2019. Supervisor: Prof. Dr. Salih Katırcıoğlu.
Keywords: Tourism Faculty; Tourism--Environmental aspects; Climatic changes--Tourism; Sustainable Tourism; Climate change, emission pollutants, tourism, global panel, islands